PENINGKATAN KEPATUHAN POLA HIDUP MELALUI PENYULUHAN KESEHATAN PADA KLIEN HIPERTENSI - Lisbeth Pardede, Renta Sianturi, Aprillia Veranita (Institut Kesehatan Hermina, 2020)
Hypertension is a chronic disease, recurring and the incidence rate is increasing annually. Hypertension required long-term handling and demanding patient awareness in the maintenance of healthy behaviours. Indeed, a large number of a patient unable to maintaining their behaviours so that needed in any way to the improvement of patient behaviours within the upkeep of their lifestyles. The research was undertaken with a quasi-experiment and be selected are 66 people by purposive-sampling and design of the pre-post test. The data collected were according to the characteristic of respondents, lifestyles obedience in consist of obedience of consumption, physical activity, rest, management of stress, controlling, and medicine intake as well. The result was any diversity of mean between before and after health education were p-value (0,000) with 95% CI. The after providing health education come about an increase in respondent knowledge which one influenced in either of attitude changes and conduct within the lifestyles. Therefore, in primary health care highly needed the health education improvement as one of the interventions client with hypertension. Keywords: hypertension, Obedience, Health Education, Lifestyle